2019
DOI: 10.1002/1878-0261.12561
|View full text |Cite
|
Sign up to set email alerts
|

miRNA expression changes during the course of neoadjuvant bevacizumab and chemotherapy treatment in breast cancer

Abstract: One of the hallmarks of cancer is sustained angiogenesis. Favorable results have been reported in some breast cancer (BC) patients receiving antiangiogenic therapy with bevacizumab (Bev) in combination with chemotherapy, and further knowledge on how Bev can be optimally combined with conventional treatment to increase efficacy is strongly needed. In this randomized, neoadjuvant phase II clinical trial, 132 patients with HER2‐negative, nonmetastatic BC were treated with Bev in combination with sequential chemot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 107 publications
1
22
0
Order By: Relevance
“…Specifically, miRNA-200a, miRNA-25 and miRNA-486-5p demonstrated 1.38-fold, 1.45-fold and 1.93-fold elevated expression in cervical cancer patients in early stages (p < 0.001). We found that most of the miRNA showed less than 2-fold level of expression differences and we hypothesized that it was due to the early stage of cervical cancer, as several studies [25][26][27] found that the cancer development at early stage did not affect miRNA expression as much as that at late stage.…”
Section: Resultsmentioning
confidence: 92%
“…Specifically, miRNA-200a, miRNA-25 and miRNA-486-5p demonstrated 1.38-fold, 1.45-fold and 1.93-fold elevated expression in cervical cancer patients in early stages (p < 0.001). We found that most of the miRNA showed less than 2-fold level of expression differences and we hypothesized that it was due to the early stage of cervical cancer, as several studies [25][26][27] found that the cancer development at early stage did not affect miRNA expression as much as that at late stage.…”
Section: Resultsmentioning
confidence: 92%
“…Particularly for cancers where new biopsies are difficult to obtain, the analysis of ctDNA can provide a tool for identifying treatment targets and monitoring treatment response, minimal residual disease and relapse. With the increasing numbers of clinical trials investigating the role of bevacizumab in cancer (ClinicalTrials.gov Identifiers NCT00790010, NCT03743428, NCT02884648, NCT03836066), commonly in combination with other drugs 2933 , the discovery of an early biomarker for treatment response, using a method that allows repetitive, minimal invasive testing at low cost, would be of high value.…”
Section: Discussionmentioning
confidence: 99%
“…The initial studies, concerning the role of miRNAs in cancer occurrence, focused on patients-derived tumoral tissues and allowed the identification of specific signature able to stratify human cancers (Lu et al, 2005;Calin and Croce, 2006;Di Leva and Croce, 2013). In particular, miRNAs discriminate tumoral from non-tumoral tissues, or metastatic from non-metastatic tumors, or different histotypes of the same tumor type, or, in treated patients, responder from non-responder individuals Lindholm et al, 2019;Sokilde et al, 2019).…”
Section: Micrornas As Potential Cancer Biomarkers In Tissues and In Bmentioning
confidence: 99%